1996
DOI: 10.1097/00006842-199605000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Family Factors Related to Alexithymia Characteristics

Abstract: There is little empirical research on the familial and parental correlates of alexithymia. A two-part study explored how the affective and cognitive characteristics of alexithymia are related to family dysfunction and maternal alexithymia. In Part I, 127 young adults were evaluated for alexithymia with the Toronto Alexithymia Scale-20 (TAS-20), for impaired imagination with the Scored Archetypal Test with Nine Elements, and for family dysfunction with the McMaster Family Assessment Device. In Part II, 80 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
5
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 28 publications
6
60
5
1
Order By: Relevance
“…Our study results cannot be compared directly to those of Berenbaum and James [14] and Lumley et al [15] because they used other research instruments that measure somewhat different aspects of parental attitude. Contrary to our expectations, perceived parental attitude was not very predictive of alexithymia or defense style.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Our study results cannot be compared directly to those of Berenbaum and James [14] and Lumley et al [15] because they used other research instruments that measure somewhat different aspects of parental attitude. Contrary to our expectations, perceived parental attitude was not very predictive of alexithymia or defense style.…”
Section: Discussionmentioning
confidence: 75%
“…To our knowledge only two empirical studies [14, 15] have been conducted on the association between childhood antecedents and alexithymia. Both studies were carried out on student populations using the Toronto Alexithymia Scale (TAS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their sample of 15 monozygotic (MZ) and 18 dizygotic (DZ) twin pairs was somewhat small, and they measured alexithymia using a brief, nonvalidated interview. Lumley et al [12]found a positive correlation between mothers’ alexithymia scores and those of their college-age children, though such results could be the result of either genetic factors or shared environmental factors. One reason to expect that alexithymia would be influenced by genetic factors is that alexithymia is associated with several characteristics, such as neuroticism, extraversion, and depression [e.g., 7, 13, 14], that have themselves been found to be genetically influenced.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, alexithymia has been found to be associated with low socioeconomic status, living alone with a lack of social relationships [13], as well as poor social skills [14]and a low level of education [15]. In addition, the development of alexithymia is thought to be connected with disturbances in the emotional atmosphere of the family during childhood [16]. Similar findings have also been found in alexithymic psychiatric patients [5, 7, 17]and other psychiatric patients [17, 18].…”
Section: Introductionmentioning
confidence: 99%